The Impact of Project-Based Learning (PjBL) Implemented through the Projek Penguatan Profil Pelajar Pancasila (P5) Project on Students’ Creativity at a Senior High School in Surabaya - Rifqi Adnis Sururi; Bening Putri Sholikhah; Safira Naila Rajab; Salsabila Dwi Yulianti (P3I UMSurabaya, 2025)
Creativity is a crucial 21st-century skill that must be developed through innovative learning models. This study aims to analyze the impact of Project-Based Learning (PjBL), implemented through the Prick Penguatan Pretil Pelaion Pancasila (PS), on high school students' creativity in Surabaya. A mixed-method approach was employed, combining a Systematic Literature Review (SLR) with qualitative descriptive field research. Data were obtained from a systematic review of four peer-reviewed articles and interviews with thirteen students who had participated in the PS program for one semester. The findings reveal that PS implementation has the potential to enhance students' creative thinking, collaboration, and problem-solving skills. However, its execution still faces challenges, including limited facilities, insufficient teacher readiness, and lack of follow-up on project outcomes. This study emphasizes the importance of teacher preparedness and instructional design in fostering a learning environment that promotes students' creativity.